The Study on the Effectiveness of Appointment Scheduling for Initial Speech Therapy Service - Chokboondee, Nicharee; Phakkachok, Sudarat; Aueworakhunanan, Tipwaree; Punkla, Weerapat (Ramathibodi Medical Journal, 2025)
Background: Many patients request speech therapy services and require long-term care. The sooner patients receive these services, the more beneficial it is for their treatment. Objectives: To study the effectiveness of appointment scheduling for the first speech therapy session and the reasons for not attending the initial session. Methods: A retrospective study, data was extracted from medical records of patients diagnosed with speech and language disorders who made an appointment with the speech and language clinic of Ramathibodi Hospital, Thailand from May to July 2022. Data was analyzed by descriptive and inferential statistics. Results: Out of 151 new patients, 108 (71.52%) attended their first scheduled appointment. Reducing the referral waiting period to less than 14 days helped improve appointment efficiency. However, there was no statistically significant relationship between referral wait time and attendance at the first speech therapy session (P = .544). The main reason for new patients not attending was due to being busy, accounting for 19 cases (53.85%). Conclusions: Reducing the referral waiting period improved appointment efficiency but did not significantly impact attendance at the first speech therapy session. Being busy was main reason for nonattendance at the first appointment.